Enhancing activated carbon supercapacitor electrodes using sputtered Cu-doped BiFeO3 thin films - Nantawat Tanapongpisit; Suchunya Wongprasod; Peerawat Laohana; Somchai Sonsupap; Jessada Khajonrit; Supansa Musikajaroen; Unchista Wongpratat; Benjaporn Yotburut; Santi Maensiri; W. Meevasana; Wittawat Saenrang (Scientific Reports, 2024)
, and over 90% retention after 1000 cycles, highlighting its durability. The uniform RF magnetron sputtering deposition is vital for mass production. Combined with impressive retention in asymmetric supercapacitors, this scalability suggests a promising pathway for large-scale manufacturing. Consequently, this work could pave the way for the large-scale production of supercapacitors.
Keywords: Supercapacitor Materials and Fabrication; Conducting polymers and applications; Advanced Sensor and Energy Harvesting Materials